Trek Angker di Sawah Basah Mampu Memperkuat Pondasi Tipe-C - I Wayan Jondra; I Made Dirgayusa; I Nyoman Sedana Triadi; Made Sudana; I Nengah Sunaya (Asosiasi Dosen Muda Indonesia, 2026)
Nowday Electrical energy consistently as an crucial role to support daily activities, so its the construction must be reliable, but incidents the corner pole construction failure also occur. It is very interesting to research, this case study to reveal the fulfillment of the technical requirements of electricity pole number NA0185 A7, to analyze the accuracy of its construction using a C-type foundation. Conducting by observations not just soil testing samples in the laboratory, but also directly in the field through sondir tests, then the data is processed statistically and mathematically. This study found that according to the technical requirements of electricity pole number NA0185 A7 constructed with a C-type pole foundation meets the technical standard and under normal condition this pole will not failure construction. This study found that on land eroded condition by irrigation water at the pole foundation base the maximum soil stress that occurs is 252.12 kN/m2, this value is much smaller than the ultimate bearing capacity (Qu) on 415.29 kN. This study also found that in wet rice fields the horizontal anchor ultimate capacity of (TuH) was 22.01 kilo Newtons, which is smaller than the horizontal force at the top of the pole, which reached 5.87 kilo Newtons, so that the anchor track would be able to protect against overturning forces. Since all technical factors have been researched and analyzed, it is reasonable to suspect that there were non-technical factors on June 21, 2021, because there was heavy rain accompanied by lightning and strong winds reaching 20 knots from the northeast) and the intensity of rain at 21.00 – 22.00 WITA was up to 25.3 mm/hour (Very Heavy), which caused the NA0185 A7 pole was down.